2020
DOI: 10.33403/rigeo.691943
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Textbook Preparation Process Supported by Instructional Technology Tools on the TPACK Self-Confidence levels of Prospective Social Studies Teachers

Abstract: The aim of this study is to determine the effect of a textbook preparation process supported by instructional technology tools on the TPACK (Technological Pedagogical Content Knowledge) selfconfidence level of prospective Social Studies teachers. The research was carried out using a sequential descriptive design with a mixed method design. Quantitative data were collected before and after the implementation process and the qualitative data were collected after the implementation process. Quantitative data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…A growing number of researchers suggest that teachers should be equipped with a well-developed technological pedagogical content knowledge (TPACK) so that they become capable of integrating appropriate technological tools in teaching (Cox & Graham, 2009). Literature review on TPACK revealed a wide range of studies conducted in different fields such as classroom training (Bayrak & Bayrak, 2021;Makawawa et al, 2021;Üredi & Ulum, 2020); preschool education (Hartati & Fahrurrozi, 2021); social studies education (Bal & Karademir, 2013;Hammond & Manfra, 2009;Knapp, 2017;Mutiani et al, 2021;Torun, 2020); Language Teaching (Adipat, 2021;Aisyah et al, 2021); Mathematics Teaching (Araujo-Filho & Gitirana, 2022;Dikkartın-Övez & Akyüz, 2013) and Science Teaching (Aktaş & Özmen, 2021;Bahriah & Yunita, 2019;Ramnarain et al, 2021). Although there are many studies on TPACK in different fields, the focus of this study is particularly on social studies teaching.…”
Section: Technological Pedagogical Content Knowledgementioning
confidence: 99%
“…A growing number of researchers suggest that teachers should be equipped with a well-developed technological pedagogical content knowledge (TPACK) so that they become capable of integrating appropriate technological tools in teaching (Cox & Graham, 2009). Literature review on TPACK revealed a wide range of studies conducted in different fields such as classroom training (Bayrak & Bayrak, 2021;Makawawa et al, 2021;Üredi & Ulum, 2020); preschool education (Hartati & Fahrurrozi, 2021); social studies education (Bal & Karademir, 2013;Hammond & Manfra, 2009;Knapp, 2017;Mutiani et al, 2021;Torun, 2020); Language Teaching (Adipat, 2021;Aisyah et al, 2021); Mathematics Teaching (Araujo-Filho & Gitirana, 2022;Dikkartın-Övez & Akyüz, 2013) and Science Teaching (Aktaş & Özmen, 2021;Bahriah & Yunita, 2019;Ramnarain et al, 2021). Although there are many studies on TPACK in different fields, the focus of this study is particularly on social studies teaching.…”
Section: Technological Pedagogical Content Knowledgementioning
confidence: 99%
“…The survey results show that the PCK competency level of the chemistry teachers who were respondents in this study is in line with the results of the PCK component analysis in the lesson plans. Most research results show teacher confidence only in PCK, not TPACK [11]. PCK is considered a basic competency that must be possessed by a teacher [9].…”
Section: Pedagogical Content Knowledge (Pck)mentioning
confidence: 99%
“…Improperly carrying out these interactions or using irrelevant or inappropriate technology for this component can lead to several negative effects [21]. All teachers who wish to integrate technology into their subjects must understand TPACK [11], [23]. Formal training in computer software for chemistry education is required but is not currently offered in many programs [24].…”
Section: Technological Pedagogical Knowledge (Tpk)mentioning
confidence: 99%
See 1 more Smart Citation
“…Measure value > 1 = very difficult item Item bias is a test condition that is unfair, inconsistent, and polluted by factors other than the ability factor to be tested. Items that are biased cause a test to be discriminatory or in favor of certain groups whose causes can be viewed from various aspects that have absolutely nothing to do with ability factors, such as gender, ethnicity, culture, region, and others (Osterlind, 1983;Torun, 2020). An item is called biased if it is found that individuals with certain characteristics are more advantageous in answering questions than individuals with other characteristics.…”
Section: Literature Reviewmentioning
confidence: 99%